Soccer seasonal variations in sprint mechanical properties and vertical jump performance - Haugen, T. A. (Kinesiology, 2018)
The aim of this study was to quantify possible differences in countermovement jump (CMJ) height, sprint performance and underlying mechanical properties as a function of time during a soccer season. Fortyfour male professional soccer players were identified in the Norwegian Olympic Federation`s test database. Each of these players had performed 40-m sprint and CMJ tests at least once within pre-season, in-season and off-season over the course of one year. The players sprinted, possibly to most likely, faster over 40 m during off-season compared to in-season (mean difference, ±90%CL: 0.04, ±0.03 s; small) and pre-season (0.08, ±0.02 s; small). Maximal horizontal power production was likely to most likely greater off-season compared to in-season (mean difference, ±90%CL: 0.5, ±0.4 W·kg-1; small) and pre-season (0.8, ±0.4 W·kg-1; small). Maximal horizontal force production was likely greater off-season compared to in-season (0.2, ±0.2 N·kg-1; small). Theoretical maximal velocity obtained during pre-season was, possibly to very likely, lower compared to in-season (0.09, ±0.12 m·s-1; small) and off-season (0.14, ±0.09 m·s-1; small). The force-velocity slope values relative to body mass were, possibly to likely, higher off-season compared to in-season (0.02, ±0.03; small) and pre-season (0.01, ±0.02; small). CMJ results obtained off-season were, likely better, than those for pre-season (1.2, ±0.6 cm; small). The present study shows that anaerobic fitness variables, believed to be relevant for the on-field soccer performance, are sensitive to the varying season times.